Climate Change, Forests and REDD : Lessons for Institutional Design. - Gupta, Joyeeta (Routledge research in international environmental law., 2013)
A search for new methods for dealing with climate change led to the identification of forest maintenance as a potential policy option that could cost-effectively reduce greenhouse gas emissions, with the development of measures for Reducing Emissions from Deforestation and Forest Degradation (REDD). This book explores how an analysis of past forest governance patterns from the global through to the local level, can help us to build institutions which more effectively deal with forests within the climate change regime. The book assesses the options for reducing emissions from deforestation i.